Perception of Muslim Students on Learning Management System - Dahlia Bonang; Any Tsalasatul Fitriyah; Dewi Sartika Nasution (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
Learning Management System (LMS) is essential for knowledge acquisition and learning management in the digital era. Users are regarded as significant stakeholders who impact the system's longevity, and their attitudes regarding the system are considered. This study compares student satisfaction levels across Moodle and Google Classroom learning platforms. This study employs a quantitative approach. A survey questionnaire was specially designed to collect data from the sample. The sample of 322 students was divided into two groups: 161 using Google Classroom and 161 using Moodle. The PIECES framework was used to quantify satisfaction. STATA's Z-test was used to examine the data in this study (mean-comparison test). According to the data, there was a difference in satisfaction with Moodle versus Google Classroom. Only one of the six criteria used to measure satisfaction shows that using Moodle with Google Classroom leads to the same level of satisfaction.